2021
DOI: 10.1080/0284186x.2021.1903077
|View full text |Cite
|
Sign up to set email alerts
|

A short report of 50 patients with gastroenteropancreatic mixed neuroendocrine–non-neuroendocrine neoplasms (MiNEN)

Abstract: The study was approved by the Danish Data Protection Agency at Rigshospitalet (ref. no. 2007-58-0015) and by the Danish Patient Safety Authority (31-1521-453). Due to the retrospective design, informed consent approval from the Ethical Committee was not required. Data collectionData were collected from the prospective NET database at Rigshospitalet and the Danish National Pathology Database. Data included gender, age at diagnosis, date of diagnosis, performance status (PS) at diagnosis, location of primary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Laenkholm et al. ( 18 ) suggested that regardless of the tumor composition, patients should be evaluated for surgical treatment, as it is related to the best prognosis. Patients with disseminated mixed tumors have a very poor prognosis and usually need adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Laenkholm et al. ( 18 ) suggested that regardless of the tumor composition, patients should be evaluated for surgical treatment, as it is related to the best prognosis. Patients with disseminated mixed tumors have a very poor prognosis and usually need adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Laenkholm et al [ 62 ], in 50 patients with GEP-MiNEN, significant prognostic factors were disease stage, surgical resection and performance status at diagnosis. Further analysis of this study reveals that MiNEN had a median overall survival (OS) of 30 months compared with NET (50 months, P < 0.001), GEP-NEC (14 months, P = 0.001) and poorly differentiated ADC (18 months, P = 0.45)[ 21 ].…”
Section: Prognosticmentioning
confidence: 99%
“…Unfortunately, their lower metastatic capacity (25% vs 54%) and longer survival time (28 vs 15 mo) relative to pure PDNEC do not change their poor prognosis[ 65 ]. Another important finding is the predictive role of the Ki-67 proliferation index of NEC for prognosis[ 15 , 66 ]. More recently, any statistically significant difference in OS between gastroesophageal GEP MiNEN vs colorectal MiNEN was detected[ 66 ].…”
Section: Organ-specific Clinicopathological Findingsmentioning
confidence: 99%
“…Another important finding is the predictive role of the Ki-67 proliferation index of NEC for prognosis[ 15 , 66 ]. More recently, any statistically significant difference in OS between gastroesophageal GEP MiNEN vs colorectal MiNEN was detected[ 66 ].…”
Section: Organ-specific Clinicopathological Findingsmentioning
confidence: 99%